Glycoconjugated Phthalocyanines as Photosensitizers for PDT – Overcoming Aggregation in Solution. Issue 42 (6th November 2019) - Bächle, Felix; Siemens, Nikolai; Ziegler, Thomas
Abstract : A series of new glycoconjugated zinc(II) phthalocyanines (Pcs) was synthesized and fully characterized. The major focus of the structural design for these new Pcs was upon the reduction of aggregate formation in solution. Therefore, the aglycons of the Pc‐linked sugars, the number and the position of the carbohydrate substituents on the Pc and the linker between sugar and Pc were varied. Specifically, di‐ and octasubstituted zinc(II) phthalocyanines with triazole and C–C linkages were synthesized and their aggregation behaviour was investigated by UV/Vis‐, CD‐ and NMR spectroscopy. The C‐glycosidically decorated Pcs described here are the first compound types of this kind. These C‐glycosidically substituted Pcs were shown to not form any aggregation in solution and hence, are considered to be potential photosensitizers in photodynamic therapy. All Pcs synthesized in this study exhibited excellent photophysical properties for use as photosensitizers ( λ max > 675 nm with εmax > 10 5 m –1 cm –1 ). Preliminary cytotoxicity studies of the Pcs presented here showed that all Pcs are photodynamically effective. Abstract : A series of glycoconjugated triazole‐and C‐glycoconjugated zinc(II) phthalocyanines was synthesized and characterized. It turned out that the aggregation behaviour in solution, promoted by the 1, 2, 3‐triazole linker, can be resolved by replacing the triazole with a C–C linkage. This led to enhanced photophysical properties of the C‐glycosylated Pcs. Cytotoxicity studies showed that these Pcs are possible candidates as photosensitizers for PDT.